2023
DOI: 10.1039/d3ta03090c
|View full text |Cite
|
Sign up to set email alerts
|

Compact nanopillar array with enhanced anti-accumulation of multiphase matter on transparent superhydrophobic glass

Abstract: Superhydrophobic glass fabricated by repeated dewetting methods yields a remarkable improvement in anti-accumulation properties of solar cells against multiphase contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…As a result, the water contact angle of the resultant Y6-NanoSH coating was >160° (Figure d) even with a roughness RMS value of about 27 nm. Previous research has shown that an acceptable rough structure scale, coating thickness control, and low-surface-energy matter are necessary for the development of a transparent superhydrophobic coating. It is exactly due to the small roughness and strong water repellency of this Y6-NanoSH coating that we ended up with an in situ photothermal, transparent, and superhydrophobic coating with a thickness (Figure S7) of about 850 nm. A dynamic and continuous bouncing behavior further illustrated that the interfacial adhesion between the Y6-NanoSH coated glass and water droplets was pretty low.…”
Section: Resultsmentioning
confidence: 98%
“…As a result, the water contact angle of the resultant Y6-NanoSH coating was >160° (Figure d) even with a roughness RMS value of about 27 nm. Previous research has shown that an acceptable rough structure scale, coating thickness control, and low-surface-energy matter are necessary for the development of a transparent superhydrophobic coating. It is exactly due to the small roughness and strong water repellency of this Y6-NanoSH coating that we ended up with an in situ photothermal, transparent, and superhydrophobic coating with a thickness (Figure S7) of about 850 nm. A dynamic and continuous bouncing behavior further illustrated that the interfacial adhesion between the Y6-NanoSH coated glass and water droplets was pretty low.…”
Section: Resultsmentioning
confidence: 98%
“…This demonstrated an effective anti-aggregation response to multiphase contaminants, suggesting its potential in advanced fingerprint resistance. 146…”
Section: Research Progress and Inherent Challenges Of Transparent Ant...mentioning
confidence: 99%
“…As a device designed for long-term outdoor use, the materials of radiative coolers are susceptible to contamination by dust and bacteria, which can potentially compromise their optical properties and thus undermine their radiative cooling performance. 26,44,45 By manipulating the composition of PMMA, it is possible to modulate the crystallization kinetics and morphology of PVDF (ZPPP film and PVDF, dashed line corresponding part in Figure 2g), thereby decelerating its rate and altering its structure, ultimately influencing its hydrophobic properties (Figure S11). 46,47 The material exhibits a higher degree of superhydrophobicity, as shown in Figure 6c, as evidenced by an increased CA from 99.75 to ∼157.5°, and a decreased SA to 2°.…”
Section: Antifouling and Stabilitymentioning
confidence: 99%
“…In the past few years, PRC based on a variety of materials and structures have been successfully prepared, which include metamaterials, , multilayer materials, , inorganic photonic structures, , and porous structures. Despite significant progress in developing efficient radiative cooling techniques, it still faces several problems that hinder its practical application, such as contamination by dust and vulnerability to bacterial contamination, especially, after the COVID-19 pandemic, there is a growing concern among the public regarding environmental health in communal spaces. The presence of bacteria associated with dust contamination may facilitate the proliferation of other microorganisms, thereby contributing to biological pollution, which cannot be overcome solely by relying on the superhydrophobic properties. Nevertheless, few works have considered the bacterial resistance of PRC materials, which are geared toward outdoor applications.…”
Section: Introductionmentioning
confidence: 99%